The Effect of Structural System Elements on the Dynamic Behavior of High-Rise Buildings - Kozan, Firdevs; Soyluk, Asena; Yılmaz, Feyza; Dallı, Mustafa (International Journal of Integrated Engineering, 2024)
The study examined whether the structure emerged as an ornament or as a result of the effort to structure the ornament in the design of the structural elements that form its facade. In particular, it focused on high-rise buildings, which have historically been an important indicator of power and prestige in relation to countries and societies. With literature review and structural classifications, it has emerged that the structure is used as an ornament in high-rise buildings designed in the architecture of the twentieth century. Three high-rise buildings based on this hypothesis were then designed. The load-bearing systems of these structures, referred to in the study as Type 1, Type 2, and Type 3, are the tubular frame system, the tubular diagrid system, and the tubular and lattice diagrid system, respectively. The structural analysis and seismic behavior of these designed buildings were carried out using the SAP2000 V 18 program according to different soil properties. The reason for including the soil properties is to see the effect of the soil on the structural performance of these three different buildings. The findings of the studies indicated that the different facade formations of these three buildings completely separated the seismic behavior of the structures from each other. Type 1, Type 2, and Type 3 have distinct structural behavior. Furthermore, the seismic behavior in rigid and soft ground conditions predicts all the factors and processes related to the facade formations and ultimately to the construction of architectural objects in high-rise buildings.